KARAKTERISASI MIKROKRISTALIN SELULOSA DARI KULIT JAGUNG PULUT (Zea mays L. Var Ceratina Kulesh) - Surya Ningsi; Nining Iklasita; Munifah Wahyuddin; Syamsuri Syakri (Universitas Islam Negeri Alauddin Makassar, 2020)
Corn husk is a part of the plant that has a high cellulose fiber content, which is around 44.08%, so it is potentially to be used as a source of raw material of microcrystalline cellulose. The purpose of this research was to synthesize and determine the characteristics of microcrystalline cellulose produced from corn husk. The making of microcrystalline cellulose was carried out in two stages, namely delignification using NaOH solvent with five variations of concentration (7,5%, 10%, 12,5%, 15% and 17,5%) and hydrolyzed using 2,5 N HCl. Characteristic test for microcrystalline cellulose included organoleptic, pH, flow time and stationary angle, FTIR, and XRD. The results showed that microcrystalline cellulose produced from corn husk had characteristics such as fine powder, white and odorless, pH was 7.0, flow time was 0.3 g/sec, a stationary angle was 54o, FTIR analysis showed a typical peak of cellulose namely 3411,05 for O-H and 2900,61 for C-H, with a crystallinity degree was 79%.